Notas ao ensino do direito em Portugal no final da Idade Média : homenagem a José Manuel Perez-Prendes - Nogueira, José Artur Anes Duarte, 1954- (2018)
Lusíada. Direito. - ISSN 2182-4118. - S. 2, n. 19-20 (2018). - p. 7-17.